Monitoring the impacts of COVID-19 in Myanmar: Food vendors - June and July 2020 survey round - Minten, Bart; Oo, Than Zaw; Headey, Derek D.; Lambrecht, Isabel B.; Goudet, Sophie (International Food Policy Research Institute, 2020)
It is feared that the COVID-19 pandemic will lead to widespread increases in global poverty and food insecurity and that these negative impacts will concentrate on the most vulnerable segments of the population (Swinnen and McDermott 2020). Although Myanmar, with one of the lowest COVID-19 infection rates in the world, has been spared the worst direct impacts of the disease, its economy remains highly vulnerable to the economic fallout of the contagion. A major contributor to increased food insecurity in Myanmar is the reduction of income among vulnerable populations (Diao et al. 2020), partly due to significant declines in remittances in the country (Diao and Wang 2020). In addition, disruptions to food marketing systems and changes in farm and consumer prices could also turn out to be major drivers of food insecurity. Changes in food markets – including supply of commodities and transport - and food and agricultural prices are an obvious concern to policy makers, given the importance of agricultural prices for the income of farmers and food prices for the purchasing power of consumers.